O anarquismo em São Paulo: as razões do declínio (1920-1935) - Bonomo, Alex Buzeli (2007)
The anarchist s influence in São Paulo didn't disappear after the strike of 1917 or in the first years of the decade of 1920 as used to be affirmed by part of the historiography on the anarchism and the labor movement. The anarchist militant s action continued to exist with great social relevance until the year of 1934. The reasons of the decline of these militant s action cannot be sought in preconceived theories or in factors that don't take into account the anarchist s formulations while protagonists of the history. In this sense, any research that looks for crumbling the reasons of the anarchist s decline it owes, in first place, to study the existent debates among the same ones. Also it must be studied among that debate the historical context in which they were inserted and for the existent international discussions on the theory, strategies and anarchist tactics. That was what we tried to develop, looking for rescuing the anarchist political statements in their newspapers, documents, texts and even in the handbooks of the Police. Using wide documentation and pertinent bibliography to each theme, in a way to accomplish a work that at the same time presented to the reader the tenor of the documentation and to brought reflections on the lifted up subjects. This way we tried to demonstrate the reasons of the decline of the anarchist s influence emphasizing their own organizing and theoretical weaknesses, not of the anarchism in general, but of the predominant anarchism in São Paulo